Differences in social isolation between young and old elderly in urban areas of Beijing, China: A cross-sectional study - Fan Wu; Yu Sheng (Elsevier, 2020)
Objectives: To understand the differences in social isolation among older adults and to identify risks associated with social isolation. Methods: Totally 485 participants aged 60 and older were recruited for this study. The Lubben Social Network Scale-6 and the Chinese version of the Medical Outcomes Study Social Support Survey were used to measure social isolation and the different types of social support that the participants experienced. Results: The proportions of young elderly (60-74 years of age) and old elderly (greater than 74 years of age) that experienced social isolation in this study were 24.4% and 33.1%, respectively. For the young elderly, three types of social support were observed to be protective factors to help avoid social isolation, and the positive effect of social support obtained from friends and neighbors was slightly stronger than that of family members. Old elderly with only a senior high school education background were at high risk of being socially isolated. Only support from friends was observed to be a protective factor for the old elderly. Conclusions: The study indicated that different ages of older adults experienced different aspects of social relationships. We propose that nursing interventions for the elderly should focus on individualized social support as a protective factor to help older adults avoid being socially isolated. Keywords: Aged, Family, Friends, Social isolation, Social support, Surveys and questionnaires